Impaired ovarian development and reduced fertility in female mice deficient in Skp2 - Fotovati, Abbas (Blackwell Science Inc, 2011)
p27 is a major negative regulator of somatic cellular proliferation, and its down-regulation has been shown to be associated with cancer development. Targeted disruption ofp27 results in complete loss of fertility in female mice, suggesting that it plays a significant role in the development of female gametes and the surrounding environment. We have now investigated the effect of loss of Skp2, an F-box protein that mediates ubiquitin-dependent degradation of p27, on female gamete production. The female Skp2-deficient mice showed accumulation of p27 in the ovary and severely compromised gamete development from the embryonic stage to follicular growth in the adult ovary, eventually leading to a decreased functional gamete reserve. Additional deletion of p27 resulted in relatively normal ovarian folliculogenesis, suggesting that accumulating p27 is primarily responsible for the compromised ovarian development. Embryonic ovaries of Skp2(−/−) mice manifested massive apoptosis as evidenced by cleavage of pro-caspase 3 and poly(ADP-ribose) polymerase-1. This in turn resulted in a significant decrease in the remaining pool of functional gametes in Skp2(−/−) mice shortly after sexual maturity and premature ovarian failure. The increased apoptosis seemed to be attributable to the polyploidy of granulosa cells. These results suggest that proper progression of the cell cycle, regulated by the p27-Skp2 axis, is pivotal for the maintenance of fertility, and that defects in this system may underlie the pathogenesis of abnormal gamete production and premature ovarian failure during the reproductive life of women.